The digital Renminbi's disruption : shaping the global economic, financial and policy landscapes - Lo, Chi (Emerald points., 2022)
China has a leading edge over the advanced countries in process of digitalisation and has created the world's first central bank digital currency, or CBDC. The business community is well aware of China's role in leading the way in global business disruption and innovation by being fast and first, global and local, and by investing in e-commerce platforms, big data, 5G network and artificial intelligence applications. Applying economic theories and data analysis, Chi Lo discusses the impact of China's digital disruption to the world's financial systems, trade and investment trends, economic policy, regulations and geopolitics. The Digital Renminbi's Disruption analyses the uncharted territories in which world is moving into, such as China's expansion of its digital infrastructure to the developing world and even advanced economies. Unique to this study is the linking of the geopolitical and China's own domestic political developments with China's digitalisation process to articulate the hidden, and often misunderstood, themes and trends both within China and the global system. Exposing hidden trends and systemic flaws and debunking myths, The Digital Renminbi's Disruption contributes to revealing China's digital disruption and leads to a better understanding of upcoming potential volatility in the wake of the unfolding digital revolution.